Developing public transport network systems: The DIANA approach - Kosmopoulos, Dimitrios I.; Kalohristianakis, M.; Malamos, Athanasios G.; Chatzis, Sotirios P.; Pternea, Moschoula; Kepaptsoglou, Konstantinos L.; Karlaftis, Matthew G. (My University, 2014)
In this paper we introduce the project DIANA, which deals with the development of innovative algorithms and decision support systems for the design of public transport network systems. The project aims to design transportation networks with conventional and electric vehicle types, with the objectives of maximizing total welfare, including the minimization of system emissions. Evolutional algorithms and reinforcement learning methods are being developed for solving the associated transit route network design problem. Finally, a web-based decision support system is under development utilizing state of the art GIS technology.
Keywords: Genetic algorithms; Reinforcement learning; Transportation systems